Comparação do método pilates a outros métodos de exercício físico no aumento da força muscular: uma revisão sistemática - Pinto, Júlia Ribeiro (2021)
Background: The Pilates method was created by Joseph initially aiming at the work of muscle strength, however, currently Pilates is indicated and known mainly for improving flexibility and balance. Knowing that muscle strength helps to maintain health and few studies have analyzed the effectiveness of the Pilates method for the muscle strength outcome, this review was carried out to address this gap in the literature and help health professionals who use the Pilates method. Design: Systematic review. Objective: To verify the effectiveness of the Pilates method compared to other physical exercise methods for the muscle strength outcome in healthy individuals. Database: The search was performed without restriction of language or year of publication in the following databases: data CENTRAL (n= 456), CINAHL (n=291), EMBASE (n= 313), PEDro (n= 176), PUBMED (n= 236), SCIELO (n= 98), SPORTSDiscus (n= 197) e Web of Science (n= 150), along with a manual search of bibliographic references. Study Selection: Randomized controlled studies that classified at least one of the comparison groups as a Pilates method and that have assessed muscle strength by comparing Pilates to another type of physical exercise were part of this review. Result: The mean score of the methodological quality of the studies assessed by the scale PEDro was from 6 ±1. For the main outcome, there was a significant difference only for the strength resistance (SMD= -0.30; 95% IC -0.58; -0.02), not being observed this difference for dynamic strength (SMD= -0.29; 95% IC -0.69; 0.10) or isometric (SMD= -0.05; 95% IC -0.55; 0.45). For secondary outcomes, there was no difference for balance and flexibility. Conclusion: There is certainly very little evidence favoring other types of exercise compared to the Pilates method for strength endurance. There is also certainty of very low to low evidence that there is no difference for dynamic strength, isometric strength, balance and flexibility.